Detection of a hydrogen corona at Callisto. Issue 5 (27th May 2017) - Roth, Lorenz; Alday, Juan; Becker, Tracy M.; Ivchenko, Nickolay; Retherford, Kurt D.
Abstract: In December 2001, the Space Telescope Imaging Spectrograph of the Hubble Space Telescope obtained far‐ultraviolet spectral images of Jupiter's moon Callisto. The leading and trailing hemispheres were observed in the spectral range 1190 Å to 1720 Å when the moon was at eastern and western elongations, respectively. We analyzed the hydrogen Lyman α (1216 Å) signal in the two observations and found that faint atmospheric emissions extending up to several moon radii away are present in addition to the solar flux reflected off the surface. We show that the detected atmospheric Lyman α emissions are consistent with an escaping hydrogen corona with a vertical column density in the range of (6–12) ×10 11  cm −2 . The derived hydrogen abundance is about 2 times higher when the moon is at eastern elongation, possibly related to increased water sublimation when the visibly darker leading hemisphere is illuminated by the Sun. The detected hemispheric difference is larger than the measurement uncertainties providing first evidence for variations in Callisto's neutral atmosphere. Plain Language Summary: Callisto, the outermost of the four large Galilean satellites, is known to have a thin atmosphere. We use 16 year old data from the Hubble Space Telescope to study its atmosphere, and we find, for the first time, the presence of atomic hydrogen. Furthermore, we find that the abundance of hydrogen changes during Callisto's orbit. The variation might be coupled to differences in the sublimation of the ice surface. The surface of one hemisphere of Callisto is darker and possibly warmer than the other, which could result in a higher sublimation rate. This would produce more water vapor, which would then produce more hydrogen, in the atmosphere above the darker hemisphere, explaining the observed variation. Key Points: Analysis of two sets of H Ly alpha images of Jupiter's moon Callisto at eastern and western elongation, which were taken in 2001 First detection of a hydrogen corona at Callisto The derived H abundance is about 2 times higher when the leading hemisphere was illuminated